Cônicas: uma forma interessante para abordar o tema no ensino médio - Zambon, Raphael Carlini (Universidade Federal de São Carlos, 2026)
The present study examines the role of manipulatives and digital technologies—specifically mathematical modeling and the use of GeoGebra—in the teaching and learning of conic sections, a topic often overlooked by high school mathematics teachers and one in which many students encounter considerable difficulty. The research investigated whether these approaches enhanced students’ understanding and performance, employing a methodology centered on practical challenges and computer-lab activities. Grounded in constructivist theory, the work emphasizes the importance of active learner engagement with the environment as a catalyst for meaningful learning. The project was designed to lead students to discover the conic sections through hands-on modeling, subsequently deepening their knowledge via theoretical instruction and enriching it with detailed exploration using GeoGebra. Group work in the creation of physical models initiated the discovery process. The lessons were developed in response to students’ questions and misconceptions arising during model construction, as well as to meet the curricular requirements of high school mathematics. Through modeling, problem-solving, and technological interaction with the conic sections, students experienced the mathematical content in a distinctive, contextualized, and engaging way. Keywords: Conic sections, Geogebra, manipulative models.
Conics: an interesting way to approach the topic in high school
Keywords: Cônicas.; Geogebra; Modelos manuais; Conics sections; manipulative models; CIENCIAS EXATAS E DA TERRA::MATEMATICA; 4. Educação de Qualidade